A Personalized Approach to Managing Patients With an Ileal Pouch-Anal Anastomosis - Ardalan, Zaid S.; Sparrow, Miles P. (Frontiers in Medicine, 2020)
Quality of life after ileal pouch anal anastomosis (IPAA) surgery is generally good. However, patients can be troubled by pouch related symptoms and pouch disorders that can be inflammatory, mechanical/surgical and functional. Management of patients with IPAA begins with measures to maintain a healthy pouch such as optimising pouch function, providing tailored advice on a healthy diet and lifestyle, screening for and addressing metabolic complications of IPAA, pouch surveillance, and risk stratification for risk of pouchitis and pouch failure. Pouchitis is the most common inflammatory disorder. Primary pouchitis is a spectrum best classified as antibiotic-responsive, antibiotic-dependant or antibiotic-refractory. It is predominately microbially mediated early on in acute antibiotic-responsive pouchitis and ends up becoming predominately immune mediated in chronic antibiotic-refractory pouchitis (CARP). Secondary prophylaxis is recommended for recurrent antibiotic-responsive and for antibiotic dependant pouchitis. Secondary causes of antibiotic-refractory pouchitis should be ruled out before a diagnosis of CARP is made. These include ischaemic pouchitis, infections such as CMV and C. difficile, coeliac disease, NSAID and Crohn’s disease (CD) of the pouch. CARP is best classified as PSC-associated, IgG4-associated and autoimmune. The former two are often associated with prepouch ileitis (PI). PSC-associated CARP and PI can be treated with budesonide or oral vancomycin. Early recognition of IgG4-associated pouchitis minimizes antibiotic use. Budesonide is used first line. Step up therapy includes immunosuppressive and biologics including anti-TNFs, vedolizumab and ustekinumab. Autoimmune CARP can be managed in a manner similar to UC. The current place of immunosuppressives in the treatment algorithm depends on availability and early access to biologic agents. Vedolizumab and ustekinumab are the preferred first- and second-line biologics for autoimmune CARP owing to their efficacy, better side effect profile and low immunogenicity and need for concomitant immunomodulatory therapy. Anti-TNF should be reserved for auto-immune CARP failing the above and for CD of the pouch. There are no guidelines for the surveillance of pouches for dysplasia. Incidence varies based on a patient’s risk. Since pouch cancer mortality is high, and surveillance is the only way to diagnose and manage neoplasia at an early stage, a risk stratified approach is recommended.